2020
DOI: 10.1101/2020.05.05.078238
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Translation-associated mutational U-pressure in the first ORF of SARS-CoV-2 and other coronaviruses

Abstract: Within four months of the ongoing COVID-19 pandemic caused by SARS-CoV-2, more than 250 nucleotide mutations have been detected in the ORF1 of the virus isolated from different parts of the globe. These observations open up an obvious question about the rate and direction of mutational pressure for further vaccine and therapeutics designing. In this study, we did a comparative analysis of ORF1a and ORF1b by using the first isolate (Wuhan strain) as the parent sequence. We observed that most of the nucleotide m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Hypermutation rather than positive selection may explain many remaining highly recurrent sites. Previous analyses showed that the rate of C>U mutation is exceptionally high relative to other mutation types in the viral genome [10,25,43,47] . This class of mutations should show increased evidence of recurring multiple times because they experience elevated mutation rates [25] .…”
Section: Recurrent Mutations Not Associated With a Lab Reflect The Mumentioning
confidence: 99%
See 1 more Smart Citation
“…Hypermutation rather than positive selection may explain many remaining highly recurrent sites. Previous analyses showed that the rate of C>U mutation is exceptionally high relative to other mutation types in the viral genome [10,25,43,47] . This class of mutations should show increased evidence of recurring multiple times because they experience elevated mutation rates [25] .…”
Section: Recurrent Mutations Not Associated With a Lab Reflect The Mumentioning
confidence: 99%
“…Extremely rapid whole genome sequencing has enabled nearly real-time tracing of the evolution of the SARS-CoV-2 pandemic [1][2][3][4][5] . By leveraging sequence data produced by labs throughout the world, researchers can trace transmission of the virus across human populations [6][7][8][9][10][11][12][13][14] . Typically, viral evolution is encapsulated by a phylogenetic tree relating all of the virus samples in a large set to one another [5,[15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…These mutations are mostly limited to point mutations, with little evidence for recombination events mediating the simultaneous transfer of multiple mutations. Although mutations may be due to RdRP/Nsp12 infidelity, the predominance of C → U and G → A mutations is consistent with base-editing defence (e.g., APOBEC/ADAR) [42,73]. The Nsp14 exonuclease-based proof-reader is a critical counter-defence against host base-editor attack on the coronavirus genome [1].…”
Section: Discussionmentioning
confidence: 99%
“…The Nsp14 exonuclease-based proof-reader is a critical counter-defence against host base-editor attack on the coronavirus genome [1]. It is also possible that the position of mutations within the genome could reflect accessibility of host base-editors to the SARS-CoV-2 genome upon uncoating, or during genome translation [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation